Principles of forming of teaching staff of orthodox educational establishments of Ukraine (1991-2001) - Larysa Roschina (Cхід, 2013)
The article is devoted the analysis of basic principles of forming of teaching staff of orthodox educational establishments of Ukraine in 1991 - 2001rr. It is well-proven that the problem of providing of pravoslavnikh of spiritual  educational establishments was settled teachers by the selection of apt at pedagogical work svyaschennosluzhiteliv and bringing in of teachers society of institute of higher. Description the processes of retraining and in-plant training teachers of spiritual educational establishments of Ukraine is given.